Modified Time-Varying Damage Model with Caputo Fractional Derivative on the Creep Destruction Prediction of Rock Slope. (8th February 2021) - Zhen, Zhi-Xin
Abstract : Based on the consideration of the time effect and connecting with typical instances, the modified Caputo fractional time-varying damage model is proposed in this paper. The parameters of creep constitutive model of slope are determined by using the powerful mathematical software and the influence of the parameters of time varying viscus element and damage element, α and ξ, on strain are shown. As α increases, the strain rates of the first and second stages of creep attenuation and steady-state stages gradually decrease and the strain rate in the acceleration stage is reflected in ξ . The fitting curve is in good agreement with the experimental data, which proves that the damage model proposed in this paper is reasonable and accurate. It provides useful reference and guidance for further study of slope creep failure and practical applications.